2014
DOI: 10.1016/j.jad.2013.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the risk for switch from unipolar to bipolar major depressive disorder in youth with ADHD: A long term prospective longitudinal controlled study

Abstract: Background Recent studies have identified subthreshold forms of bipolar (BP)-I disorder and deficits in emotional regulation as risk factors for bipolar disorder in youth. The primary aim of this study was to investigate whether emotional dysregulation and subthreshold forms of BP-I disorder increase the risk for BP switches in ADHD youth with non-bipolar MDD. Methods We used data from two large controlled longitudinal family studies of boys and girls with and without ADHD. Subjects (N=522) were followed pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…In the first study by Biederman et al (2009a), the investigators reported that subthreshold symptoms of mania were significantly overrepresented in children with ADHD who developed bipolar-I disorder at follow-up compared with those who did not (70% vs 17%, p¼ .002). A subsequent report by Biederman et al (2013) using data from the same sample reported a significantly increased risk for manic switches in ADHD children with baseline MDD with subthreshold symptoms of mania when compared with those without such symptoms (57% vs 21%;OR¼9.57, p¼.013).…”
Section: Subthreshold Manic Symptomsmentioning
confidence: 90%
See 2 more Smart Citations
“…In the first study by Biederman et al (2009a), the investigators reported that subthreshold symptoms of mania were significantly overrepresented in children with ADHD who developed bipolar-I disorder at follow-up compared with those who did not (70% vs 17%, p¼ .002). A subsequent report by Biederman et al (2013) using data from the same sample reported a significantly increased risk for manic switches in ADHD children with baseline MDD with subthreshold symptoms of mania when compared with those without such symptoms (57% vs 21%;OR¼9.57, p¼.013).…”
Section: Subthreshold Manic Symptomsmentioning
confidence: 90%
“…Children with CHT also displayed a wider range of aggressive behavior and a higher rate of suicidality (suicidal ideation in 81% vs 36%, po .05). Likewise, Biederman et al (2013) reported that ADHD children with deficient emotional self-regulation (defined by 41SD and o2SD elevations in the Anxiety/ Depression, Aggression, and Attention subscales of the CBCL) had a significantly increased risk for manic switches (OR ¼3.54, p¼ .037).…”
Section: Emotional Dysregulationmentioning
confidence: 98%
See 1 more Smart Citation
“…Follow-up studies have shown that the rates of diagnostic change to full-blown BD are significantly higher in HCL-32(+) patients than the rates in HCL-32(-) patients (Biederman et al, 2014;Holma et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…This switching of diagnosis from unipolar depression to BD is up to more than 30 % within a 5-year period, and it is significantly higher in children in comparison to adults (Geller and Luby 1997 ). It is also higher for youths with attention defi cit hyperactivity disorder (ADHD) with subthreshold bipolar features at baseline (57 % vs. 21 %) as well as in those with defi cient emotional self-regulation (Biederman et al 2014 ). ADHD is frequently comorbid with BD and both disorder share many clinical and neurobiological features (Galanter and Leibenluft 2008 ).…”
Section: Clinical Features Of Paediatric Bdmentioning
confidence: 99%